A REFLECTION ON FOREIGN LANGUAGE ENJOYMENT DURING VOCABULARY LEARNING WITH ACTIVELY LEARN IN A LOW-ANXIETY LEARNING ENVIRONMENT - Mutiara Bilqis (Kopertis Region IV Jabar and Banten, 2023)
Research on effective vocabulary learning has been vastly related to the enforcement of extensive reading in or outside the class. Somehow, the idea of bringing extensive reading to Indonesian EFL context seems like quite a challenge considering the literacy level of the country. This research focuses on the reflection on foreign language enjoyment students’ experience during vocabulary learning through extensive reading in Actively Learn which was done a low-anxiety learning environment. The data were taken from 43 freshmen’s and the teacher’s written reflections during and after 8-week meetings. The data were analyzed using semantic-deductive thematic analysis. The results show that students struggled at first due to reading long texts, but later they enjoyed the learning process and reading materials due to 1) enjoyable and fun atmosphere, 2) getting lots of knowledge about phrasal verbs, collocations, and idioms, 3) mistakes being tolerated as part of learning process, 4) variations of activities, and 5) meanings of difficult words are discussed and described in gestures and depictions.